Student’s Achievement of Learning Competencies and Challenges in Learning World History in Public High Schools - Delaben, Rudylyn; Bual, Joel; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
World History is essential among students in understanding the past civilizations that shape the current generations. Thus, this study assessed the students' achievement of learning competencies in World History in geography, early civilization, and the world in the classical and transitional periods relative to sex, family monthly income, parent's highest educational attainment, and teacher's highest educational attainment. It also identified challenges encountered in World History and investigated achievement differences relative to demographics. Using quantitative design, 269 stratified randomly sampled students responded to the researcher-made multiple-choice questionnaire. A checklist identified the challenges. The data were analyzed using mean, standard deviation, frequency count, percentage distribution, Mann-Whitney, and Kruskal Wallis. Meanwhile, the researcher adhered to the Philippine Health Research Ethics Board (PHREB). Generally, they have a proficient level of achievement. In challenges, the students lack interest in reading and have difficulty memorizing. Regarding teachers, most fail to connect the lessons to real-life situations and neglect to give student feedback. In a learning environment, the school has inadequate instructional resources, the library contains outdated materials, and the environment at home is not conducive to studying. In subject, topics are complex to understand, and contents are heavy. However, differences exist in their achievement relative to parents' educational attainment and sex. Hence, improvement in world History focuses on the challenges identified and continuous improvement of teaching strategies to elevate the achievement of learning competencies in World History. Also, the results partially validated the theory. With these, further studies are recommended to validate the claims. Also, the results partially validate the theory. With these, further studies are recommended to validate the claims.